Toxicity Test of Methanol Extract of Neem (Azadirachta indica) Leaves on Instar III Larvae (Bactrocera spp) - Almaheran, Sundus Sepia; Artayasa, I Putu; Bahri, Syamsul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Azadirachtin, alkaloids, saponins, tannins, and flavonoids are some of the secondary metabolites found in neem leaves. These compounds have natural insecticidal activity and function as antifeedants or repellents to effectively inhibit the growth and development of insect pests. This study investigates the effects of neem leaf extract (Azadirachta indica) as a natural pesticide on the mortality of fruit fly larvae (Bactrocera spp.) found in starfruit (Averrhoa carambola L.). We conducted experiments using various concentrations of neem leaf extract: 0%, 4%, 9%, 14%, 17%, and 19%. The fruit fly larvae were treated with the extract for 6 hours, and the mortality rates were subsequently observed. The results demonstrated a positive correlation between increasing concentrations of neem extract and higher larval mortality rates. The highest concentration of 19% resulted in a mortality rate of 95%. One-Way ANOVA statistical analysis showed a significant effect of the extract on larval mortality (p < 0.05). The Tukey HSD test revealed significant differences in mortality rates between concentrations of 9% and above when compared to the control and lower concentrations. The LC50 value was calculated at 15.263%, indicating that neem leaf extract is effective as a larvicide. Neem leaf extract contains secondary metabolites such as azadirachtin, alkaloids, saponins, tannins, and flavonoids, which likely induce larval death through morphological damage to the digestive organs and head. This study concludes that neem leaf extract is a promising botanical pesticide for controlling fruit fly pests in starfruit.